MEMBANGUN KARAKTER SISWA YANG UNGGUL DAN BERAKHLAK MULIA DI ERA KURIKULUM MERDEKA - Maliana Julia Saputri; Santiani Santiani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study explores how the Merdeka Curriculum builds character in Indonesian students by integrating moral, ethical, and national values within classroom practices and extracurricular activities. Through library research, various academic sources, books, and policy documents were reviewed to synthesize existing evidence on holistic character education. The findings indicate that the curriculum not only emphasizes academic achievement but also promotes active learning methods—such as project-based learning and student-centered discussions—that enhance students’ critical thinking, creativity, and social responsibility. In particular, the incorporation of civic education and tolerance helps students internalize values like honesty, responsibility, and patriotism. Challenges identified include variations in teacher readiness and infrastructural limitations, highlighting the need for ongoing professional training and better resource allocation. Overall, the Merdeka Curriculum offers a promising framework for developing well-rounded, morally upright individuals who can meet modern educational and societal demands.